1995
DOI: 10.1074/jbc.270.28.16903
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-induced Conformational Changes in the ATPase and Substrate Binding Domains of the DnaK Chaperone Provide Evidence for Interdomain Communication

Abstract: Interactions of the DnaK (Hsp70) chaperone from Escherichia coli with substrates are controlled by ATP. Nucleotide-induced changes in DnaK conformation were investigated by monitoring changes in tryptic digestion pattern and tryptophan fluorescence. Using nucleotide-free DnaK preparations, not only the known ATP-induced major changes in kinetics and pattern of proteolysis but also minor ADP-induced changes were detected. Similar ATP-induced conformational changes occurred in the DnaK-T199A mutant protein defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
272
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(311 citation statements)
references
References 48 publications
37
272
1
1
Order By: Relevance
“…To verify the suitability of MABA-ADP and MABA-ATP for measuring Hsc70 and Hsp70 nucleotide exchange kinetics, we determined the mutual exchange rates of MABA-ADP versus ADP and MABA-ATP versus ATP. ADP and ATP exchange rates were independently measured using the intrinsic fluorescence of the single tryptophan that was shown to change in response to ATP binding (26,27). The measured rates were very similar, and the fluorescent analogs were therefore suitable for the nucleotide exchange experiments.…”
Section: Association and Dissociation Of Fluorescent Nucleotidementioning
confidence: 99%
“…To verify the suitability of MABA-ADP and MABA-ATP for measuring Hsc70 and Hsp70 nucleotide exchange kinetics, we determined the mutual exchange rates of MABA-ADP versus ADP and MABA-ATP versus ATP. ADP and ATP exchange rates were independently measured using the intrinsic fluorescence of the single tryptophan that was shown to change in response to ATP binding (26,27). The measured rates were very similar, and the fluorescent analogs were therefore suitable for the nucleotide exchange experiments.…”
Section: Association and Dissociation Of Fluorescent Nucleotidementioning
confidence: 99%
“…In all of these processes, DnaK is thought to interact transiently with unraveled segments of partially unfolded or denatured protein substrates. Studies have shown that the reversible switching from a high affinity conformation, which binds substrate tightly, to a low affinity conformation, which binds substrate weakly, is the hallmark of DnaK activity (7)(8)(9)(10)(11). Such a mechanism is shown in Scheme 1, where ADP⅐DnaK⅐P and ATP⅐DnaK* are the high and low affinity states, respectively, and E and J are GrpE and DnaJ, respectively.…”
mentioning
confidence: 99%
“…ATP binding to the Nterminal domain induces a global conformational change in DnaK (7) which is thought to displace the lid from the top of the ␤-sandwich subdomain, creating the low affinity form of the protein. To gain insight into the function of the lid, slightly different lidless forms of DnaK and eukaryotic Hsp70s have been engineered (9,(15)(16)(17)(18). What has emerged from these studies is that loss of the lid does not interfere with interdomain coupling (15), and loss of the lid results in a 2-20-fold increase in K d values for peptide interaction with the ADPbound state of lidless DnaK (17,18).…”
mentioning
confidence: 99%
“…1A) (1,8). These co-chaperones are important because the ADP-bound form of Hsp70 has a tighter affinity for substrates than the ATP-bound state (31). Thus, J proteins are expected to promote tight binding of Hsp70s to their substrates and these co-chaperones have been found to play multiple roles during protein aggregation (21,32).…”
mentioning
confidence: 99%